The Perceived Impact of the COVID-19 Pandemic on the Social Needs of Adult Emergency Department Patients (Mary Ann Liebert, 2022)
Objectives: We aim to assess the influence of COVID-19 on the social needs of emergency department (ED) patients, and assess patients' access to social services. Methods: We conducted a cross-sectional survey of 175 purposively sampled adult ED patients. Results: Approximately half of participants stated that COVID-19 negatively impacted their social needs with statistically significant differences observed for race, ethnicity, and insurance status. Many participants did not know of available social services, and a majority welcomed assistance from the ED. Conclusion: This study suggests that unmet social needs have risen because of COVID-19, and EDs may be positioned to identify and assist affected patients.